Insulin-like growth factor I gene promoter polymorphism, collagen type II α1 (COL2A1) gene, and the prevalence of radiographic osteoarthritis: the Rotterdam Study - Zhai, G (2004)
Objective: To examine the role of an IGF-I gene promoter polymorphism in the prevalence of radiographic osteoarthritis (ROA), and study its interaction with the COL2A1 gene. Methods: Individuals genotyped for IGF-I (n = 1546) and COL2A1 gene polymorphisms (n = 808) were selected from a random sample (n = 1583) derived from the Rotterdam study. The presence of ROA was defined as a Kellgren score of 2 or more in at least one of four joints (knee, hip, hand, and spine). Genotype specific odds ratios (OR) were adjusted for age, sex, body mass index, and bone mineral density using logistic regression. Interaction with the COL2A1 genotype was tested. Results: Overall, no association was found between the IGF-I polymorphism and ROA. In subjects aged 65 years or younger (n = 971), the prevalence of ROA increased with the absence of the 192 base pair (bp) allele (p for trend = 0.03). Compared with homozygotes for the 192 bp allele, the prevalence of ROA was 1.4 times higher in heterozygotes (95% confidence interval, 1.0 to 1.8) and 1.9 times higher in non-carriers (1.1 to 3.3). There was evidence of interaction between the IGF-I and COL2A1 genes. Individuals with the risk genotype of both genes had an increased prevalence of ROA (OR 3.4 (1.1 to 10.7)). No effect was observed in subjects older than 65 years. Conclusions: Subjects with genetically determined low IGF-I expression (non-carriers of the 192 bp allele) may be at increased risk of ROA before the age of 65 years. Furthermore, an interaction between the IGF-I and COL2A1 genes is suggested.